ADAPTASI SPASIAL RUMAH PASCA-BENCANA DENGAN STRUKTUR FLEKSIBEL DAN STRUKTUR PERMANEN - Akbar Preambudi; Annisa Oktareangga Dheany (Jurnal Teknik Sipil dan Arsitektur, 2025)
The earthquake that struck Yogyakarta and its surrounding areas in 2006 caused significant physical damage across the region. Post-disaster reconstruction was carried out through various housing assistance programs. These programs produced diverse housing types that varied in architectural form, structural systems, and distribution mechanisms. Two notable examples of such housing are the dome houses in Ngelepen Village, Sleman, and the core houses in Tembi Village, Bantul. These two types of post-disaster dwellings reflect different structural approaches in terms of their capacity for spatial growth and transformation. Dome houses were designed with a fixed structural system, limiting future expansion, while core houses were built with a flexible structural concept, allowing for spatial modification and extension. Almost two decades after the earthquake, both housing types have undergone significant spatial adaptations in response to the evolving needs of their inhabitants. This study aims to evaluate how residents have spatially adapted to the design of these post-disaster homes and how such adaptations relate to their spatial cognition. The findings reveal both differences and similarities in the patterns of spatial adaptation between the two housing models, highlighting the influence of initial structural design on the subsequent spatial transformation. This research contributes to a deeper understanding of post-disaster housing resilience and resident-driven spatial evolution over time.